Karakteristik Fisikokimia dan Sensoris Es Krim Ubi Jalar Ungu (Ipomoea Batatas L.) Dengan Subtitusi Pemanis Ekstrak Daun Stevia (Stevia Rebaudiana Bertoni M.) dan Berbagai Jenis Stabilizer - Bambang Nugroho; Arif Prashadi Santosa; Solihin Amirudin (UM Purwokerto Press, 2021)
This study aims to determine the effect of sweetener concentration, various types of stabilizers and their interactions on proximate, antioxidant and sensory content of ice cream. The study was conducted using a Factorial Completely Randomized Design (CRD) consisting of two factors. The first factor is the comparison of sweetener concentration with 3 levels of 100% sugar sweetener (D1), 50% sugar sweetener: 50% stevia extract sweetener (D2) and 100% stevia extract sweetener (D3) while the second factor is the type of stabilizer with 3 levels namely, agar. - agar (S1), Gelatin (S2) and CMC (S3). The results obtained were analyzed using the F test and followed by the DMRT test with a confidence level of 95%. The results showed that the comparison of sweetener concentration (D) and treatment interaction (DxS) had a significant effect. While the sensory analysis has a significant effect on the texture, taste, overall variables and does not significantly affect the aroma variable. The best treatment in the proximate analysis of sensory analysis is the treatment of using 50% sugar and 50% stevia and agar-agar (D2S1) stabilizer with the organoleptic score of fragrance, texture, taste and preference respectively were 3.80 (normal); 3.60 (slightly soft); 3.80 (good); 4.10 (liked), and the Physicochemical value of overrun, melting time, fibre content, viscosity, antioxidant, and sugar content respectively were 42,5%; 14,06 minutes; 0,3107%; 1,217 cP; 11,65%; 20,33%.